COVID-19 mandated self-directed distance learning: Experiences of Saudi female postgraduate students - Alghamdi, Amani (Journal of University Teaching and Learning Practice, 2021)
Since the emergence of the 2020 coronavirus (COVID-19) pandemic, Saudi Arabia (SA) has preserved the safety of its citizens by mandating crisis distance education (CDE). Appreciating that most learners struggle with such an abrupt shift in delivery mode, especially one that depends on self-directed learning (SDL), this exploratory, qualitative study solicited data in May 2020 from a convenience sample of 20 Saudi female postgraduate students enrolled at a public university in the Eastern Province of SA. Findings affirmed that SDL via CDE contributed to their educational growth, and they will continue to engage with SDL after the health crisis ends. In short, their SDL CDE experience changed the way they will approach their education in the future. Their high level of SDL allowed them to assume responsibility for their learning. They especially gained an appreciation for the role of reflection, self-monitoring, and self-evaluation. SDL both instilled and promoted self-confidence, self-reliance, commitment, and perseverance. Implications for future research were tendered and universities are encouraged to intentionally build learning environments that support learner-centered and self-directed learning to move the country through and beyond the COVID 19 pandemic.